Pengaruh Fintech, Sikap Keuangan, dan Lingkungan Sosial Terhadap Perilaku Keuangan Mahasiswa di Kota Batam - Lusi Susanti; Dian Efriyenti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study was prompted by the massive escalation in the use of financial technology (fintech) among students, particularly in Batam City, which serves as a competitive industrial and service hub. Although this digital innovation offers transaction convenience, unrestricted access has the potential to lead to consumptive behavior if not balanced with a mature financial attitude and a supportive social environment. Based on this phenomenon, this study aims to evaluate the influence of fintech, financial attitude, and social environment on the financial management behavior of Accounting students in Batam City. The research approach used is descriptive quantitative with a survey questionnaire method. The study sample involved 267 respondents selected through purposive sampling, with the size determined using the Slovin formula to ensure data representation. All data were analyzed statistically using multiple linear regression via IBM SPSS Statistics 30. The research findings reveal that fintech, financial attitude, and social environment consistently provide a significant influence on students' financial behavior, both partially and simultaneously. In conclusion, the integration of intelligent technology utilization, sound personal financial principles, and a positive social ecosystem are the main determinants in creating disciplined, healthy, and accountable financial management in the digital economic era.